Psychophysiological and affective reactions of female students to short high-intensity interval training with own body weight - A.V. Moment (Theory and Practice of Physical Culture, 2023)
Objective of the study was to objectify the psychophysiological and affective reactions of recreationally inactive female students to short high-intensity interval training with their own body weight (whole-body HIIT). Methods and structure of the study. 10 recreationally inactive healthy students of Pskov State University took part in the experiment. Subjects were asked to perform a short whole-body HIIT workout consisting of 10 stimuli lasting 30 seconds, alternating with 30 seconds of passive rest. After each stimulus, individual perception of the load and affective valence were assessed. The performed motor cycles were counted. Heart rate was recorded throughout the workout. Results and conclusions. Affective valence during training decreased on average in the group from 3.9±1.1 and 0.5±2.6 points, and individual perception of the load linearly increased on average in the group from 3.3±0.8 to 6.6 ±1.3 points, in the absence of a significant decrease in physical performance. The reaction of the cardiovascular system during the implementation of the experimental protocol objectively corresponded to the parameters of high-intensity training, at the same time, the results of the analysis of affective reactions suggest that for the majority of recreationally inactive female students this protocol will be comfortable enough to perform.